Oral Sulfate Solution versus Polyethylene Glycol as a Single-Day Preparation for Colonoscopy: A Randomized Control Trial - Shah, Bhavik Bharat; Patel, Bubun; Goenka, Mahesh Kumar (Journal of Digestive Endoscopy, 2019)
Background Colonoscopy is a principal diagnostic tool for most colonic disorders. Adequate bowel preparation is essential for proper visualization of the mucosa. The aim of this study was to compare the tolerability, efficacy, and safety profile of 1 L of oral sulfate solution (OSS) in comparison to 2 L of polyethylene glycol (PEG) solution.Methods In this single-center prospective study conducted at our institute, patients were randomly assigned to receive either OSS or PEG solutions for colonoscopy preparation. Patients enrolled in either group completed a questionnaire assessing the taste of the solution used, adverse effects, and number of stools passed. Grading of the bowel cleansing quality was done as per Boston Bowel Preparation (BBP) score.Results Total of 400 patients, with 222 patients in the PEG group and 178 patients in the OSS group, were assessed. In the PEG group, 148 (66.75%) patients were males and in the OSS group 112 (62.9%) patients were males. There was no statistical significance on comparison of the taste as “good” or “bad” in both groups. All the adverse events were mild to moderate in intensity and their frequencies were comparable for both the groups. The OSS group had better bowel preparation as per the BBP score (p = 0.021) and lesser cecal intubation time (p = 0.028).Conclusion The present study demonstrated that 1 L of OSS is better than the well-established 2 L PEG solution, in terms of bowel preparation and shorter time to cecal intubation.
Keywords: colonoscopy preparation; oral sulfate solution; polyethylene glycol